2022
DOI: 10.1007/s00170-022-10151-0
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth analysis of tool wear mechanisms and surface integrity during high-speed hard turning of AISI D2 steel via novel inserts

Abstract: Over the years, machinists have been exploring the hard part turning of AISI D2 steels. Initially, cylindrical grinding was used for this purpose, but it was later replaced by single-point turning due to its advantages such as high material removal, low cost, and greater flexibility. Conventional inserts are used in single-point turning, but they have been reported to have large radial forces, high notch wear, and poor surface finish. Therefore, multi-radii wiper inserts were designed to overcome these machini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Surface roughness decreases by 33.6% with an increasing value of spindle speed [ 49 , 50 ] from 6500 rpm to 7500 rpm, as higher spindle speed increases the machining temperature that softens the fibres of the workpiece and makes their cutting easy by leaving fewer ups and downs in the walls of the holes (as evident from Figure 9 ). A similar effect was observed by Ishida et al [ 51 ] during helical milling of CFRP stacks while working under different machining temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Surface roughness decreases by 33.6% with an increasing value of spindle speed [ 49 , 50 ] from 6500 rpm to 7500 rpm, as higher spindle speed increases the machining temperature that softens the fibres of the workpiece and makes their cutting easy by leaving fewer ups and downs in the walls of the holes (as evident from Figure 9 ). A similar effect was observed by Ishida et al [ 51 ] during helical milling of CFRP stacks while working under different machining temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more research is needed to contribute to stakeholders' knowledge on the workshop floor for decision-making and informed planning in machining AISI D2, owing to its importance and various application in manufacturing technology. Considering the contrary views of results, on which of process parameters (cutting speed, depth of cut, and feed rate) influences surface roughness most; as reported by [28,32,33], the feed rate is most significant compared to the depth of cut and cutting speed. Furthermore, [29] reported that cutting speed was the most significant factor, while [2] and [45] suggested depth of cut as most significant compared to feed rate and cutting speed.…”
Section: Introductionmentioning
confidence: 98%
“…The results show that the ML models provided better prediction accuracy and the optimization methodology reduced cost more than the traditional techniques with constant optimized cutting parameters. Khan et al [32] comprehensively analyzed surface integrity and tool wear during the hard turning of AISI D2 using novel prime inserts. It was reported that feed rate has a higher effect on the workpiece surface roughness than the depth of cut while cutting speed had an insignificant effect.…”
Section: Introductionmentioning
confidence: 99%
“…High-speed machining is an advanced technology that can produce high-precision products and reduce the costs associated with the assembly and storage of fixtures [1]. High-speed machining offers advantages such as fast metal removal rate leading to increased machining productivity, low cutting force, and good surface quality [2][3][4][5]. During high-speed machining, the chip moves out of the cutting zone faster, significantly reducing the cutting heat because the cutting heat is transferred mainly to the chip [6].…”
Section: Introductionmentioning
confidence: 99%